PENGARUH METODE PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTU WORDWALL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS VI DI MI DAARUL AITAM PALEMBANG - Echa Silvia; Ahmad Syarifuddin; Agra Dwi Saputra; Tutut Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the current educational landscape, student-centered and interactive learning methods are increasingly important for improving learning outcomes. However, the implementation of innovative teaching strategies is often limited by the availability of effective learning media. This study aimed to examine the effect of the Team Games Tournament (TGT) learning method assisted by Wordwall on the science learning outcomes of sixth-grade students at MI Daarul Aitam Palembang. The research employed a quantitative approach using a quasi-experimental design, specifically the Nonequivalent Control Group Pretest–Posttest Design. Samples were selected through purposive sampling, and data were collected using observation, tests, and documentation. Data analysis included validity, reliability, discrimination, difficulty level, normality, homogeneity, and hypothesis testing. The findings revealed that the experimental class achieved a mean post-test score of 84.56, while the control class obtained a mean score of 68.75. The Independent Samples t-Test produced a significance value of 0.000, which is lower than 0.05, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. These results demonstrate that the TGT learning method supported by Wordwall has a significant positive effect on students’ science learning outcomes. The study suggests that integrating game-based cooperative learning with digital media can enhance student engagement, motivation, and academic achievement. Therefore, the application of TGT assisted by Wordwall can serve as an effective and enjoyable strategy for improving science learning in elementary schools.